2018
DOI: 10.1111/ijd.14234
|View full text |Cite
|
Sign up to set email alerts
|

Infectious skin disorders encountered in a pediatric emergency department of a tertiary care hospital in Argentina: a descriptive study

Abstract: Background Infectious skin disorders (ISDs) are commonly seen in pediatric emergency departments (PED), however the exact frequency is unknown. We provide an accurate evaluation of the incidence and characteristics of ISDs diagnosed in a PED from Buenos Aires, Argentina, over a 1-year period.Methods Prospectively, descriptive study of children evaluated in the PED with ISDs during 2016. ISDs were analyzed on the basis of their incidence, patient demographics, seasonal variations, and hospitalization rates.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 42 publications
1
5
2
Order By: Relevance
“…Of these, 3 conditions-urticaria, atopic dermatitis, and contact dermatitis-represented 31% of all consultations. This finding differs from other studies, where infections represented 34% to 67.9% 4,9,11,13,14 of dermatologic consultations in ED.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Of these, 3 conditions-urticaria, atopic dermatitis, and contact dermatitis-represented 31% of all consultations. This finding differs from other studies, where infections represented 34% to 67.9% 4,9,11,13,14 of dermatologic consultations in ED.…”
Section: Discussioncontrasting
confidence: 99%
“…4 When we analyzed specific diagnoses, viral skin infections were the most frequent condition, similar to that reported in the literature 1,4,11 ; however, other authors have reported bacteria as the most common infection, specifically streptococcal and staphylococcal infections. 9,13 Although there are some differences among these studies, most agree that ISD and infections are the most common diagnoses seen at the ED. 1,4,9,11 In our study, these two groups represent more than 75% of all consultations.…”
Section: Discussionmentioning
confidence: 97%
“…This result corresponds with a trend found in another university hospital in Central Thailand, 3 as well as in school children in Hong Kong 6 in which there was a shift away from cutaneous infection to eczematous disease for being the most prevalent pediatric skin disease. However, this pattern differs from that found in some countries, such as India, 7 Napal, 8 Turkey, 9 and Argentina 10 where infectious cutaneous diseases are still predominant.…”
Section: Discussioncontrasting
confidence: 75%
“…Viral infections were most common in the West[817] similar to ours, but bacterial infections were common in India[4] and Argentina. [18] The pattern of viral infections seen in our study reflects the general Indian pattern. Hand foot and mouth disease was the most common viral infection in ours but unreported from the West,[2] where varicella was the commonest reported exanthem.…”
Section: Discussionsupporting
confidence: 59%